Lithium Dependent Electrochemistry of p‐Type Nanocrystalline CuCrO2 Films. Issue 23 (14th November 2022) - Chown, Amanda L.; Yeasmin, Humaira; Paudel, Rajendra; Comes, Ryan B.; Farnum, Byron H.
Abstract: CuCrO2 nanocrystals were synthesized and fabricated into mesoporous thin films to study their electrochemical properties, where a strong [Li + ] dependence was observed. An anodic shift in the Cu 2+/+ redox potential was observed with increased [Li + ] in the electrolyte, in addition to the growth of a new redox feature at E1/2 =−0.43 V vs Fc +/0 . This new feature was attributed to Cu 2+/+ redox chemistry accompanied by Li + occupation in copper vacancy surface defects. The equilibrium constant and maximum charge for Li + occupation were determined to be K=0.057 M −1 and 15.5 mC, respectively. The maximum charge was close to the expected value of 11 mC based on the measured concentration of copper vacancies. The pronounced Li + dependent electrochemistry suggests that CuCrO2 behaves similarly to cathodes in Li‐ion batteries. Thus, chronopotentiometry experiments revealed a 7.8 mA h g −1 charge capacity at cycle 2 and increasing cycling efficiency from 83 to 91 % over 10 cycles. However, a pronounced decrease in charge capacity was observed with increased cycles, attributed to a loss in lithium‐coupled electrochemistry. These studies add to our understanding of surface defects in p‐type oxides and their effect on hole recombination in solar cell devices. Abstract : Electrochemistry of CuCrO2 : The electrochemistry of CuCrO2 nanocrystals shows a pronounced dependence on Li + cations, assigned to lithium coupled redox chemistry at copper vacancy surface defects sites. Such defect sites could play important roles in interfacial electron transfer reactions within solar cell devices.